PENGARUH RETURN ON ASSET (ROA), DEBT TO EQUITY RATIO (DER), CURRENT RATIO (CR), DAN TOTAL ASSETS TURNOVER (TAT) TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG MASUK DALAM KATEGORI INDEKS LQ-45 DI BURSA EFEK INDONESIA - Zamzami, Karlina Karimah; Afif, M Nur (Universitas Djuanda, 2015)
This study aimed to examine the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), and Total Assets Turnover (TAT) to return the stock at a manufacturing company in the category of LQ-45 index in Stock Securities Indonesia. The study was conducted using quantitative methods with a total sample of 20 companies is determined by purposive sampling method. Method of hypothesis testing using F test, t-test, and multiple linear regression. The results is Return on Assets (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), and Total Assets Turnover (TAT) effect on stock returns. As partial the Return on Assets (ROA) and Total Asset Turnover (TAT) significantly influence stock returns. While the Debt to Equity Ratio (DER) and the Current Ratio (CR) does not significantly affect stock returns.Key Words : Return on Asset, Debt to Equity Ratio, Current Ratio, Total Assets Turnover, and Stock Return.